ISOLASI DAN KARAKTERISASI BAKTERI LAUT DARI OBJEK WISATA PUSAT LAUT DESA TOWALE KABUPATEN DONGGALA SULAWESI TENGAH - Nugraini, Shinta; Permatasari, Ghita; Mutasim, Kholid; Humairah; Ifandi, Slamet; Lastri Gintoe, Hermin (Universitas Cokroaminoto Palopo, 2024)
The Sea Center is a tourist attraction on the beach in the form of a natural well located in Towale village. Because it is unique and is widely used by the community for bathing, this tourist attraction needs to be researched to determine its potential, one of which is through the exploration of marine bacterial species, plus the research conducted is still very lacking or even non-existent. The purpose of this study was to isolate and characterize marine bacteria. The results showed that there were 6 isolates of marine bacteria obtained, namely isolates PS1, PS2, PS3, PS4, PS5, PS6. Macroscopic characterization observations obtained colony shape, elevation shape and shape of the most dominant edges are irregularly shaped, convex and flat. While microscopic observations obtained the nature of marine bacterial isolates, namely 4 isolates are Gram positive coccus-shaped and 2 isolates are Gram negative bacillus-shaped.